Inactivation of Vibrio parahaemolyticus in drinking water - Mahadeva Iyer, K., Sanjeev, S. and (Fishery Technology, 2021)
A study was conducted in the Cochin area of India to determine the effect of drinking water on Vibrio parahaemolyticus, a bacterium that contaminates fish harvested from marine and estuarine environments. Times of fresh-water exposure required to inactivate these bacteria are given. Findings indicate that the washing of fish and equipment used to handle the fish in drinking water may decrease in the number of viable Vibrio cells and thus aid in prevention of food poisoning.